SOLUTION OF THE THERMAL CONDUCTIVITY EQUATION OF A RODS WITH A SQUARE SECTION BY THE DIFFERENCE METHOD - Mazakov Т.Ж.; Kalimoldayev М.Н.; Dzhomartova Ш.А.; Begaliyeva К.; Mazakova Ә.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The purpose of this work is to study the thermophysical state of a rod of constant cross section and limited length. A three-dimensional body is considered, the constant cross section of which has the shape of a square. It is assumed that the left end of the rod coincides with the origin of coordinates and the heat transfer coefficient is assumed to be constant over the entire surface of the rod. It is also assumed that the rod is subject to point temperature and surface heat transfer. The stated problem is solved by the difference method, i.e. the heat equation is approximated by a difference scheme. A program has been developed for finding the temperature distribution along the rod, which places the results of numerical calculations in several files. The results of numerical calculations in dynamics (over time) are displayed in the form of one-dimensional and two-dimensional graphs.